Islamic Perspective Roles on the World Civilization Development - M Bustanul Ulum (STAIFAS-Press, 2023)
The world civilization over time continuously experiences development. Many forms of thought or civilization that developed have an impact on the civilization progress that exists today. The interesting discussion is about how Islamic perspectives contribute to the world’s development of civilization. This article has some question foundations. The method that is applied is descriptive qualitative with an interpretive approach. This writing concludes that Islamic perspectives greatly contributed to world civilization throughout mainland Europe. This is proved by the existence of various Muslim figures with their respective perspectives. Whether related to astronomy, medicine, sciences, and natural sciences or social sciences including philosophy, theology, and social sciences. The Islamic perspective contributions have also happened in various areas of life such as politics, economics, and society